Nd3+‐Yb3+/Nd3+‐Yb3+‐Li+ co‐doped Gd2O3 phosphors for up and down conversion luminescence. (2nd March 2018) - Ranjan, Sushil Kumar; Soni, Abhishek Kumar; Rai, Vineet Kumar
Abstract: Frequency up‐conversion (UC) emission from the Nd 3+ ‐Yb 3+ /Nd 3+ ‐Yb 3+ ‐Li + co‐doped gadolinium oxide (Gd2 O3 ) phosphors prepared by the solution combustion technique in the visible range have been studied by using 980 nm near infrared (NIR) laser diode excitation. The crystalline structure and formation of the cubic phase has been confirmed with the help of X‐ray diffraction (XRD) studies. XRD peak shifts have been found towards the lower diffraction angle side in the case of the Nd 3+ ‐Yb 3+ ‐Li + co‐doped phosphors. Surface morphology and particle size information have been observed by using field emission scanning electron microscopy (FESEM) and transmission electron microscopy (TEM) analysis. Down‐conversion emission study under 351 nm excitation in the visible region for the Nd 3+ ‐Yb 3+ /Nd 3+ ‐Yb 3+ ‐Li + co‐doped phosphors has been performed. The UC emission bands lying in the green and red region arising from the Nd 3+ ions have been enhanced by 260 times, 113 times due to incorporation of Li + ions in the Nd 3+ ‐Yb 3+ co‐doped phosphors. Photometric characterization has been done for the Nd 3+ ‐Yb 3+ /Nd 3+ ‐Yb 3+ ‐Li + co‐doped phosphors. The present study suggests the capability of the synthesized phosphors in near‐infrared (NIR) to visible upconverter and luminescent device applications.